The Effect of Geometrical Parameters on Heat Transfer Characteristics of Compact Heat Exchanger with Louvered Fins. (14th November 2012) - Gunnasegaran, P.; Shuaib, N. H.; Abdul Jalal, M. F.
Abstract : Compact heat exchangers (CHEs) have been widely used in various applications in thermal fluid systems including automotive thermal management systems. Among the different types of heat exchangers for engine cooling applications, cross-flow CHEs with louvered fins are of special interest because of their higher heat rejection capability with the lower flow resistance. In this study, the effects of geometrical parameters such as louver angle and fin pitch on air flow and heat transfer characteristics on CHEs are numerically investigated. Numerical investigations using five different cases with increased and decreased louver angles (+2°, +4°, −2°, −4°, and uniform angle 20°), with a fixed fin pitch and using three different fin pitches (1.0 mm, 2.0 mm, and 4.0 mm), and with the fixed louver angle are examined. The three-dimensional (3D) governing equations for the fluid flow and heat transfer are solved using a standard finite-volume method (FVM) for the range of Reynolds number between 100 and 1000. The computational model is used to study the variations of pressure drop, flow temperature, and Nusselt number.